2015
DOI: 10.1007/s00192-014-2622-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic maximum urethral closure pressures measured by high-resolution manometry increase markedly after sling surgery

Abstract: Advanced HRM technology to measure MUCPs under cough and strain conditions without withdrawal techniques provides new insights into the continence mechanism after tension-free MUS: MUCPs do not change at rest but do increase significantly during cough and strain maneuvers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The most common procedure to treat incontinence when related to urethral hypermobility is the midurethral sling (MUS). Work by our group has already demonstrated that after MUS placement there is no significant change in maximum urethral closure pressures (MUCP) at rest, but marked increases (up to 60 cm H 2 O) with cough, and strain . These findings suggest that the MUS does not affect the urethra at rest, but functions by augmenting the MUCP during cough, and strain maneuvers.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…The most common procedure to treat incontinence when related to urethral hypermobility is the midurethral sling (MUS). Work by our group has already demonstrated that after MUS placement there is no significant change in maximum urethral closure pressures (MUCP) at rest, but marked increases (up to 60 cm H 2 O) with cough, and strain . These findings suggest that the MUS does not affect the urethra at rest, but functions by augmenting the MUCP during cough, and strain maneuvers.…”
Section: Introductionmentioning
confidence: 84%
“…Each study subject completed three validated incontinence symptom questionnaires before and 6 weeks after urethral bulking injection: the Incontinence Severity Index (ISI, scale 0‐12), the Incontinence Impact Questionnaire Short Form (IIQ‐7, scale 0‐100), and the Urogenital Distress Inventory short form (UDI‐6, scale 0‐100) . This urethral bulking cohort was compared to a cohort of 26 patients who underwent the same HRM measurements before and after MUS placement . The study was approved by the University of California San Diego Institutional Review Board and written informed consent was obtained from each participant.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations